Surgical practice in Uruguay during the COVID-19 Pandemic: Analysis of qualitative and quantitative aspects of its initial phase. - Perdomo Pérez, Mauro Andrés; Ruso Martínez, Luis; Olivera Pertusso, Eduardo; Rodríguez Temesio, Gustavo; González González, Daniel (Cirugía del Uruguay, 2020)
Due to the SARS-CoV-2 infection pandemic in Uruguay, guidelines and recommendations were established that radically modified the usual surgical procedures. These measures were based on recommendations based on previous international experience, tending to perform only urgent / emergency surgeries, oncological patients and those who cannot be postponed. Objective. Analyze the impact of the COVID-19 pandemic on the practice of surgical specialists in our country. Material and methods. A survey was carried out and disseminated through the scientific surgical societies of Uruguay, which was kept open for a period of 10 days (April 20 to 30, 2020), collecting a total of 262 responses, of which 212 were complete. . Results: 52% of those surveyed performed scheduled surgeries and 55% performed video-assisted approaches; 51% of those who performed surgeries denied having taken additional protective measures during them. Twenty-three (9%) of the specialists operated on patients suspected of carrying Covid. 19 and 3 (1.1%) positive COVID-19 cases. 57% considered themselves "partially trained" and 21% "poorly trained" (21%), while 19% defined themselves as "fully trained" for the use of protection elements. Conclusions: High compliance with the suspension measures for coordination surgeries was verified (decrease of 82). Surgeries in patients with COVID-19 were exceptional and the frequency of cases with suspected disease was low. The excess of information and the existence of multiple protocols have determined considerable heterogeneity in the implementation of protection measures and low participation in training activities.